2015
DOI: 10.1016/j.sbspro.2015.06.322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Innovation Types on Performance of Manufacturing Firms in Turkey

Abstract: The purpose of this study is to explore the effects of innovation types on the firm performance. This study was conducted on 197 manufacturing firms cted to the data. The questions of the innovation types measure were determined by Günay (2007) from the typology of Oslo Manual (OECD, 2005). The author determined the questions of the firm performance measure based on the Balanced Scorecard approach. The product innovation, process innovation and organizational innovation have positive impacts on financial perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0
30

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 6 publications
8
102
0
30
Order By: Relevance
“…An important relation of MI with RPA supported the finding of previous studies, such as Rodriguez (2006), andNaidoo (2010). While the important relation of MI with MP supported the findings of previous studies, such as Johnson et al (2009), Hoonsopon andRuenrom (2012), Sok et al (2013), Rosli and Sidek (2013), and Karabulut (2015). The finding indicated that the improvement of market innovation at religion based market would improve religio-centric positional advantage and market performance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…An important relation of MI with RPA supported the finding of previous studies, such as Rodriguez (2006), andNaidoo (2010). While the important relation of MI with MP supported the findings of previous studies, such as Johnson et al (2009), Hoonsopon andRuenrom (2012), Sok et al (2013), Rosli and Sidek (2013), and Karabulut (2015). The finding indicated that the improvement of market innovation at religion based market would improve religio-centric positional advantage and market performance.…”
Section: Discussionsupporting
confidence: 84%
“…Marketing innovation is defined as the ability to implement a concept or a new marketing strategy which is different from the common marketing methods used by the company, including changes in the design or in product packaging, distribution, promotion and price of a product that is intended to increase the market penetration of goods, services and increase sales (Moreira et al, 2012;Karabulut, 2015). Marketing innovation is described using three dimensions, namely innovation in the product, associated with changes in the physical product; innovation in the service, associated with changes in the customer service process by utilizing available resources effectively and efficiently; and innovation in delivery rate including changes in the logistics and channels used to deliver the product to the buyer (Kim and Mauborgne, 1997).…”
Section: Marketing Innovativeness (Mi)mentioning
confidence: 99%
“…In figure 2, yearly distribution of those articles are shown. (Chen, 2008;Garcia-Valderrama et al, 2008;GarciaValderrama et al, 2009;Bigliardi and Dormio, 2010;Wang et al, 2010;Ghazinoory and Soofi, 2012;Khota and Pretorius, 2012;Jarrar and Smith, 2014;Rylková and Bernatík, 2014;Zizlavsky, 2014) Information Systems and Knowledge Management (Bhargava et al, 2007;Harlow, 2008;Amberg and Lang, 2009;Asosheh et al, 2010;Han, 2011;Lopez-Nicolas and Merono-Cerdan, 2011;Wu and Chang, 2012;Loukis and Charalabidis, 2013;Wu and Chen, 2014) Finance & Management Accounting (Rom and Rohde, 2007;Zhao, 2007;Granlund, 2011;Belfo and Trigo, 2013;Chenhall and Moers, 2015;Yiannaki, 2015 (Huang et al, 2011;Karabulut, 2015;Noori, 2015) Corporate Social Responsibility & Sustainability Leon-Soriano et al, 2010;Wang, 2013;Álvarez, 2015) Method Specific (ANN, AHP) (Savetpanuvong and Tanlamai, 2008;Quezada and LopezOspina, 2014) © 2017 AESS Publications. All Rights Reserved.…”
Section: The Balanced Scorecard Approachmentioning
confidence: 99%
“…Within the study, fuzzy analytic hierarchy process and balanced scorecard are applied to explore the algorithms and procedures in detail whilst seeing the BSC as a useful framework for evaluating the innovation performance of the organization. Karabulut (2015) on the other hand, conducted a study of manufacturing firms in Turkey to observe the company performance from the innovation strategy point of view. The author indicates that designing attractive strategies for innovation yields high company performance.…”
Section: Social Servicesmentioning
confidence: 99%
“…A research by Mathivathanan et al [23] identify several elements for the company performance, among others are company profitability, company flexibility, customer satisfaction, and employee satisfaction. Karabulut [24] conducts a research on manufacturing companies in Turkey using Balanced Scorecard to measure the performance and uses the criteria as follows: the company financial performance, the customer satisfaction performance, the internal process performance, and the learning and growth performance.…”
Section: Business Performancementioning
confidence: 99%